STUDI PENGEMBANGAN PENYEDIAAN AIR BERSIH DARI MATA AIR DI DUSUN III LANCANG DESA PEGAGAN JULU III KECAMATAN SUMBUL KABUPATEN DAIRI TAHUN 2014 - Johannes LRS; surya dharma; evi naria (Lingkungan dan Kesehatan Kerja, 2014)
Water is a basic need for life, especially for the human being who during his life always require water. The water used is not always in accordance with the terms of health because the water is often containing germs or certain substances that can cause illness and even endanger human survive. This study was descriptive survey method. The population in this study were 105 heads of households and the samples were 51 householders. Samples were taken by using a sytematic random sampling technique. The purpose of this study was to determine the visibility of water supply from springs in Dusun III Lancang Desa Pegagan Julu III Kecamatan Sumbul Kabupaten Dairi. Based on the research results, the existing water source in Desa Pegagan Julu III met the physical and chemical quality (pH, Fe, Mn, Zn, Cd, Pb, Hg, Al), quantity and continuity requirements as a source of clean water. The level of respondent knowledge about clean water and water supply was categorized as moderate (78%). The participation form of community in the construction of water supply were their time (82%), skill (72%) and fund (100%). Stakeholders support the development of water suplly as the availability of clean water sources, the potential of natural resources and  community support for construction of clean water supply. Therefore we need an active role of health provider to give health promotion about clean water supply in order to improve the knowledge of community to clean water and clean water supply. In addition, it is expected the participation of  stakeholders and the community in cooperation with the private sector, Non-Governmental Organizations (NGOs) and the organizer PNPM so that the clean water supply in Dusun  Lancang III can be realized.